ChemInform Abstract: Radiolabeled Heterobivalent Peptidic Ligands: An Approach with High Future Potential for in vivo Imaging and Therapy of Malignant Diseases. Issue 33 (25th July 2013) - Fischer, Gabriel; Schirrmacher, Ralf; Waengler, Bjoern; Waengler, Carmen
Abstract Review: ca. 50 refs.